Ai-Based Building Security System Using Vision Tracking Motion Method - Mustofa, Bisri; Sujadi, Harun; Wahyuni, Tantri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Security is something that is needed by every human being, because with security there will be an impression of comfort. Especially in a place of residence or a place to carry out economic transactions or even an agency. Artificial intelligence is a form of scientific discipline which is an artificial intelligence that functions to facilitate the process of human life technologically. Machine Learning is a machine that was developed to be able to learn by itself without direction from the user. Video tracking motion is a method that is used as a reference to capture movement in objects that change position which is translated on the process frame motion system. An application related to Artificial Intelligence (AI) which can control automatically regarding the video camera system in the form of IPCam and Analog UsbCam, with a database as a medium for storing the results of video capture images regarding process frames that exceed the limit, which functions for security in a place in the form of house or building.